Isolation of endophytic actinomycetes from roots and leaves of maize (Zea mays L.) - Araújo,Janete M. de (2000)
Actinomycetes were isolated from surface sterilized leaves and roots of maize. A total of 53 isolates were obtained, 31 of them from leaves and 22 from roots. The genus Microbispora was the most frequently found followed by the genera Streptomyces and Streptosporangium. From the isolated actinomycetes, 43.4% showed antimicrobial activity against one or more tested bacteria and yeast.